Blockchain-Assisted Privacy-Preserving Intrusion Detection for Secured Metaverse (International Journal of Food and Nutritional Sciences, 2022)
The increasing popularity and adoption of virtual reality (VR) and augmented reality (AR) technologies have led to the emergence of the metaverse, a virtual universe where users can interact and engage in various activities. However, the metaverse's growing complexity and interconnectedness introduce new security challenges, making it vulnerable to intrusion attempts and privacy breaches. This research paper proposes a blockchain-assisted privacy-preserving intrusion detection system for ensuring the security of the metaverse environment. The system leverages the decentralized and immutable nature of blockchain technology to enhance intrusion detection while preserving user privacy.